Pengaruh Gender dan Usia Dewan Terhadap Kinerja Keuangan - Sinta Ramaiyanti; Mayla Khoiriyah; Arumega Zarefar; Ulfa Afifah; Atika Zarefar (Jurusan Akuntansi Politeknik Negeri Padang, 2023)
This study aims to examine the effect of board gender and board age on company performance using Market to Book Ratio (MBR) measures, measuring board gender using the percentage of female commissioners from the total commissioners while board age using board age data. The study used a quantitative descriptive approach using panel data from agricultural companies listed on the Indonesia Stock Exchange with an observance period from 2014 – 2018. Data was analyzed with Ordinary Least Square using Stata. The results showed that the gender of the board had a significant negative influence on the company's performance. In other words, the participation of female board members has a positive impact to some extent. Meanwhile, the age of the board positively affects the company's performance. Older board members have experience and are more careful in making decisions. Decisions are made based on experience and can collaborate with younger board members. In addition, older board members have the ability to take strategic decisions and have less chance of going bankrupt. This research contributes to the consideration of the selection of the composition and composition of the board of directors of a company, especially public companies.